The ethics of sports coaching - Hardman, Alun; Jones, Carwyn 1967- (Ethics and sport, 2011)
Is the role of the sports coach simply to improve sporting performance? What are the key ethical issues in sports coaching practice? This book argues that the coaching process is an inherently moral one with an inescapably ethical dimension, involving intense relationships between players and coaches.